Avaliação das características do concreto produzido com a cinza do bagaço da cana-de-açúcar em substituição parcial do cimento Portland e sua viabilidade econômica. - Abreu, Ennes do Rio (2021)
Portland cement is one of the most consumed materials in civil construction, however, there is a large CO2 emission in the production of cement, consequently there is a search for alternative materials in construction that reduce environmental impacts and production costs. As Brazil is one of the main world producers in the sugar and alcohol complex, sugarcane represents great importance for agribusiness in the country's economy. Bagasse is a by-product of sugarcane that, during burning in boilers, is generated from sugarcane bagasse ash (CBCA). With the advances in research, it was found that the predominance of chemical compounds from the sugarcane bagasse ash is silicon dioxide (SiO2). The objective of this research is to evaluate the mechanical properties and the influence of the characteristics of the partial replacement of CBCA in proportions of 10%, 15% and 20% and 0% as a reference, in the durability of the concrete produced with Portland cement of the type CPV ARI with respect to water / binder 0.55. For durability analysis, specimens were made, where they were analyzed by electrochemical techniques for corrosion evaluation, through the corrosion potential test (Ecorr), corrosion intensity (Icorr), resistivity and polarization resistance. Still in relation to durability, the morphological characterization of the particles was carried out with identification of the chemical elements present by the scanning electron microscopy (SEM) technique. As well, pozzolanicity, the mineralogical and chemical composition of the materials were evaluated using the X-ray diffraction (XRD) technique and Fourier transform infrared (FTIR) spectroscopy. On economic feasibility, bibliographic surveys were carried out for better support and research findings. The obtained results indicate as crystalline phases SiO2, Fe2O3, KAlSiO4 and Al (PO3)3, showing that the specimens produced with CBCA reached more electronegative values of corrosion potential over time, providing a more favorable condition for corrosion. Concluding that the physical-chemical characteristics of the ashes depend significantly on the degree of crystallinity of the bagasse fibers, on the granulometry of the ashes and on the burning conditions of the bagasse and that CBCA is an industrial residue with great availability, being able to substitute the cement in low contents with significant advantages.